2021
DOI: 10.3389/fimmu.2021.599530
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Inclusion of Black Soldier Fly (Hermetia Illucens) Larvae Meal and Paste Improved Gut Health but Had Minor Effects on Skin Mucus Proteome and Immune Response in Atlantic Salmon (Salmo Salar)

Abstract: The present study investigated effects of dietary inclusion of black soldier fly larvae (BSFL) (Hermetia illucens) meal and paste on gut health, plasma biochemical parameters, immune response and skin mucus proteome in pre-smolt Atlantic salmon (Salmo salar). The seven-week experiment consisted of seven experimental diets: a control diet based on fishmeal and plant protein (Control-1); three BSFL meal diets, substituting 6.25% (6.25IM), 12.5% (12.5IM) and 25% (25IM) of protein; two BSFL paste diets, substituti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
33
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 42 publications
(37 citation statements)
references
References 114 publications
(177 reference statements)
4
33
0
Order By: Relevance
“…Using insects as feed in aquaculture is advantageous when compared to fishmeal not only for ecological reasons but also for sustainability [ 91 , 92 ] and animal health [ 93 , 94 , 95 ]. The extensive use of fishmeal brings dangers such as transmitting of fish-associated pathogens and other pollutants to farmed marine animals.…”
Section: Discussionmentioning
confidence: 99%
“…Using insects as feed in aquaculture is advantageous when compared to fishmeal not only for ecological reasons but also for sustainability [ 91 , 92 ] and animal health [ 93 , 94 , 95 ]. The extensive use of fishmeal brings dangers such as transmitting of fish-associated pathogens and other pollutants to farmed marine animals.…”
Section: Discussionmentioning
confidence: 99%
“…HILM contains higher or similar protein content and richer essential amino acid content ( Yu et al, 2020 ). During recent decades, many studies indicated that the significant effects of HILM on intestinal health ( Weththasinghe et al, 2021 ). Intestinal morphology and intestinal microbiota are critical to maintaining ecosystem stability and performance.…”
Section: Discussionmentioning
confidence: 99%
“…The soluble proteins contained in the supernatant were stored at −20 °C until use. The cytokine TNF-α was determined following the indirect ELISA method described by Morales-Lange [ 59 ], with slight modifications according to Weththasinghe [ 33 ]. Briefly, 100 µL of sample diluted to 45 ng/µL in a carbonate buffer (60 mM NaHCO 3 , pH 9.6) were seeded into 96-well plates (NUNC MAXISORPTM, Invitrogen), and incubated overnight at 4 °C.…”
Section: Methodsmentioning
confidence: 99%
“…These and other published data support the idea that, with the due differences among species, a partial replacement of FM with IM has no adverse effects on the growth of most fish. Moreover, functional properties such as a possible enhancement of both the immunological and the antioxidant systems have been attributed to IMs, possibly due to compounds such as chitin or its derivatives [ 14 , 21 , 29 , 30 , 31 , 32 , 33 ].…”
Section: Introductionmentioning
confidence: 99%